COMPARISON OF ZERO ZONE CATALOGUES OF THE FON PROGRAM BASED ON THE KYIV AND KITAB OBSERVATIONS - Andruk, V. M.; Relke, H.; Protsyuk, Yu. I.; Muminov, M. M.; Ehgamberdiev, Sh. A.; Yuldoshev, Q. X.; Golovnia, V. V. (Одеські астрономічні публікації, 2016)
The two new catalogues for the zero zone of the FON project were created after the processing of two different collections of digitized photographic plates. The photographic plates were received at the DAZ and DWA telescopes of the Kitab observatory of the Republic of Uzbekistan (KO UAS) and of the Main astronomical observatory in Kyiv (MAO NASU) in the number of 90 and 120 plates, respectively. The digitization of these photographic plates in the frame of the Ukrainian Virtual Observatory project was performed by means of the Epson Expression 10000XL scanner with the scanning resolution of 1200 dpi. The coordinates of stars and galaxies for the both catalogues are determined in the system of the Tycho2 catalogue. The stellar magnitudes of all objects are done in B-magnitudes of the photoelectric standard system. The difference between the calculated and the reference positions is equal σαδ = ±0.06–0.07". The internal accuracy of the both catalogues for all objects is σ αδ = ±0.20", σB = ±0.18m and σ αδ = ±0.27", σ B = ±0.17m, respectively. We present the comparison of these both catalogues with each other and with the Tycho2, UCAC4 as well as PPMX catalogues and discuss the results.